Improving indonesian writing ability and how to Write the value of money with audio visual media at Second grade students of sd negeri 28 pasar gompong Kecamatan lengayang - Nurlis Nurlis (Fakultas Sastra Universitas Ekasakti, 2017)
This classroom action research is motivated by several factors, including the lack of students' ability to write short stories. The problem in thisresearch is how improve the students' ability to write stories Indonesian (BI) and ways of writing money by using audio-visual media. This study aims to improve students' ability to write stories and ways of writing the value of money by using audio-visual media, writing back with their own words you've already watched the film becomes an example. This study is a quantitative and qualitative. The method used in this research is the method of observation and tests. Setting this study in SDN 28 Gompong Market District of Lengayang , which is in Class II SD Negeri 28 Market Gompong totaling 32 students . The process of execution of the actions carried out in two cycles, and each cycle consists of four stages from planning, action, observation and reflection stages. The results of quantitative research in the first cycle with the results of 69% (average grade) and 69% (the number of students who pass the study). While on the second cycle showed an increase in 84% (average grade) and 100% (the number of students who pass the study). From this study it can be concluded that by using audio-visual media can improve the ability to write short stories and ways of writing the value of money Class II SD Negeri 28 Gompong Market